The Effect of Groundwater Quality Towards Resistivity - Che Ariffin, Hajar Shahirah; Madun, Aziman (Recent Trends in Civil Engineering and Built Environment, 2023)
Electrical Resistivity Method (ERM) is widely used as a geophysical method in groundwater investigation. This study will observe the effect of groundwater quality towards resistivity, focusing on acidity (pH) and iron (Fe) content. The objectives of these studies are to investigate the effect of pH and Fe2+ concentration on electrical resistivity value and to compare the resistivity values obtained by stimulated groundwater quality. The methods used were Electrical Resistivity Method (ERM) and pH test based on ASTM 1293 – 18. It was observed that the neutral pH, pH 7 with the lowest concentration of Fe, 8 mg/l, shows the optimum values that nearest to groundwater resistivity value which is 10 Ohm.m. The resistivity value increased along with the pH level. However, after the pH level passed the neutral level, the resistivity values dropped. The resistivity responds with the presence of different pH levels and Fe concentrations. It was suggested to increase the variation of groundwater quality to obtain more accurate results to compare with the groundwater’s resistivity.